Razones para crecer en la empresa familiar: Un análisis comparativo - G. Fuentes Lombardo; M. J. Hernández Ortiz; M. C. Vallejo Martos (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2008)
Growth is considered a very important strategic goal for family and non family firms. However, due to the singularities of family firms and the overlap of their three different systems (family, management and ownership), their reasons to grow can be different from non family firms. The results of this empirical research in the Spanish wine Industry show that when familiness is higher, the growth is motivated more for family than for business reasons. On the other hand, when the firms show a less familiness, growth as a strategic goal is more motivated for business reasons. At the same time, reasons to justify growth are different if the managers of the company are or not members of the owned family.
Keywords: 330; family firm; growing; wine industry; goals